ACCRETION, DISPERSAL, AND REACCUMULATION OF THE BISHUNPUR (LL3.1) BRECCIATED CHONDRITE - EVIDENCE FROM TROILITE-SILICATE-METAL INCLUSIONS AND CHONDRULE RIMS - Kojima T.; Lauretta D.S.; Buseck P.R. (My University, 2003)
A set of troilite-silicate-metal (TSM) inclusions and chondrule rims in the Bishunpur (LL3.1) chondrite provide information regarding impact brecciation of small bodies in the early solar system. The TSM inclusions and chondrule rims consist of numerous angular to subrounded silicate grains that are individually enclosed by fine networks of troilite. FeNi metal also occurs in the troilite matrix. The silicates include olivine (Fo55-98), low-Ca pyroxene (En78-98), and high-Ca pyroxene (En48-68Wo11-32). Al- and Si-rich glass coexists with the silicates. Relatively coarse silicate grains are apparently fragments of chondrules typical of petrologic type-3 chondrites. Troilite fills all available cracks and pores in the silicate grains. Some of the TSM inclusions and rims are themselves surrounded by fine-grained silicate-rich rims (FGR).The TSM inclusions and rims texturally resemble the troilite-rich regions in the Smyer H-chondrite breccia. They probably formed by shock-induced mobilization of troilite during an impact event on a primitive asteroidal body. Because silicates in the TSM inclusions and rims have highly unequilibrated compositions, their precursor was presumably type-3 chondritic material like Bishunpur itself. The TSM inclusions and the chondrules with the TSM rims were fragmented and dispersed after the impact-induced compaction, then reaccreted onto the Bishunpur parent body. FGR probably formed around the TSM inclusions and rims, as well as around some chondrules, during the reaccumulation process. Components of most type-2 and 3 chondrites probably experienced similar processing, i.e., dispersal of unconsolidated materials and subsequent reaccumulation.